Kegiatan Adaptasi Teknologi pada Penugasan Program Kampus Mengajar 4 di SMP N 2 Kalabahi - Oktofina Meriance Lonawata; Ronapli Blegur Wabang; Lois Letidena; Jeni Marianti Loban; Melki Imamastri Puling Tang (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Technology is an inseparable part of society in the 4.0 era, the enthusiasm to create a technology literate generation is contained in various policies in the world of education. The Teaching Campus Program is one of the flagship programs of the Ministry of Education, Culture, Research and Technology (Kemendikbudristek) policy. The Teaching Campus Program is a program that provides opportunities for students to learn outside the classroom by becoming teacher partners in the learning process at the basic education level. By participating in Campus Teaching activities, students will have the opportunity to hone their soft skills and character, as well as gain teaching experience that can be recognized in the form of semester credit units (credits). The Teaching Campus Program is a collaboration whose beneficiaries are university students and students at the elementary and junior high school education levels. This program focuses on two outputs, namely competency development for program participant students through capacity building for leadership, creativity and innovation, problem solving, communication, team management, and improvement of analytical thinking, as well as increased literacy and numeracy for students in target schools. This context is getting stronger considering the condition of literacy and numeracy in Indonesia which is still low along with efforts to increase literacy and numeracy as one of the national priority agendas